1995
DOI: 10.1001/jama.1995.03530020067034
|View full text |Cite
|
Sign up to set email alerts
|

The Greater Risk of Alcoholic Cardiomyopathy and Myopathy in Women Compared With Men

Abstract: Despite the fact that the mean lifetime dose of alcohol in female alcoholics was only 60% that in male alcoholics, cardiomyopathy and myopathy were as common in female alcoholics as in male alcoholics. This finding, together with a more pronounced response of the ejection fraction to the dose of ethanol, indicates that women are more sensitive than men to the toxic effects of alcohol on striated muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
1
7

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(109 citation statements)
references
References 36 publications
3
98
1
7
Order By: Relevance
“…Women absorb and metabolize alcohol differently than men 33 and women seem to be more sensitive than men to the toxic effects of alcohol on cardiac function, developing alcoholic cardiomyopathy with a lower total lifetime dose of alcohol compared with men. 734 Consistent with these findings, our study shows associations between alcohol intake and subclinical changes in cardiac structure in both sexes; although only among women increasing alcohol intake was associated with mild reduction of ventricular systolic function. In consequence, this study gives strength to the differences in the sensitivity of toxic alcohol effects by sex, which is in agreement with the international recommendations for a lower threshold of alcohol consumption in women compared to men.…”
Section: Figuresupporting
confidence: 88%
“…Women absorb and metabolize alcohol differently than men 33 and women seem to be more sensitive than men to the toxic effects of alcohol on cardiac function, developing alcoholic cardiomyopathy with a lower total lifetime dose of alcohol compared with men. 734 Consistent with these findings, our study shows associations between alcohol intake and subclinical changes in cardiac structure in both sexes; although only among women increasing alcohol intake was associated with mild reduction of ventricular systolic function. In consequence, this study gives strength to the differences in the sensitivity of toxic alcohol effects by sex, which is in agreement with the international recommendations for a lower threshold of alcohol consumption in women compared to men.…”
Section: Figuresupporting
confidence: 88%
“…These results have important clinical implications given evidence that alcohol use in women is increasing [3] and that women experience more adverse health consequences related to alcohol use [47]. Operant procedures that incorporate both appetitive and consummatory parameters will be useful in identifying individual differences in AUD and determining if treatments should be targeted at different phases of the treatment process depending on whether reducing craving or consumption is the treatment goal.…”
Section: Discussionmentioning
confidence: 99%
“…For example, compared to older cohorts, younger cohorts of women report a higher percentage of frequent binge drinking while these percentages have decreased in younger cohorts of men [3]. These findings are concerning given that women are more susceptible to negative health consequences associated with alcohol use [47]. …”
Section: Introductionmentioning
confidence: 99%
“…Ethanol ingestion is toxic for muscle and leads to the rapid appearance of ultrastructural changes [11]. Furthermore, women seem to be at higher risk of alcoholic cardiomyopathy and myopathy than men [12]. In our study, the discrepancy in the percentage of patients with increased CPK level observed between men and women is a possible argument for this fact.…”
Section: Discussionmentioning
confidence: 60%